Existence, concentration and multiplicity of positive solutions for an elliptic system inRN - Argomedo Salirrosas, Segundo Manuel (2022)
Tese (Doutorado em Matemática) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Matemática, Brasília, 2022.